The Coevolution of Stellar Wind-blown Bubbles and Photoionized Gas. II. 3D RMHD Simulations and Tests of Semianalytic Models - Lachlan Lancaster; Chang-Goo Kim; Jeong-Gyu Kim; Eve C. Ostriker; Greg L. Bryan (The Astrophysical Journal)
In a companion paper (Paper I), we presented a coevolution model (CEM) in which to consider the evolution of feedback bubbles driven by massive stars through both stellar winds and ionizing radiation, outlining when either of these effects is dominant and providing a model for how they evolve together. Here we present results from 3D radiation magnetohydrodynamical simulations of this scenario for parameters typical of massive star-forming clouds in the Milky Way: precisely the regime where we expect both feedback mechanisms to matter. While we find that the CEM agrees with the simulations to within 25% for key parameters and modestly outperforms previous idealized models, disagreements remain. We show that these deviations originate mainly from the CEM’s lack of (i) background inhomogeneity caused by turbulence and (ii) time-variable momentum enhancements in the wind-blown bubble (WBB). Additionally, we find that photoionized gas acts similarly to magnetic fields by decreasing the WBB’s surface area. This causes a decrease in the amount of cooling at the WBB’s interface, resulting in an enhanced WBB dynamical impact.